Upaya Meningkatkan Nilai-Nilai Moderasi Beragama Di STAI Muhammadiyah Blora Melalui Penguatan Pemahaman Kaidah Kaidah Ushul Fiqih - Nurhartanto, Armin (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2022)
Shari'ah according to the linguistic meaning is something that is commonly heard in life, and we are used to using it in the learning process at school, especially when delivering worship or shari'a materials. Then what exactly is the semantic meaning or linguistic meaning. Manna' Al Qathan in his book al-Tasyri' wa al fiqh fi al islam, mentions that shari'ah means all the provisions of allah that are shari'a for his servant's servant, both regarding aqidah, worship, mu'amalah and akhlaq (Qathan, t.th,:15). Thus according to him shari'a is the same as religion which includes aspects of worship, aqidah, mu'amalah and also akhlaq. His view is almost in line with Faruq Nabhan who states that shari'a is everything that Allah preaches to his servant servant (Nabhan 1981: 10). But he further stated that, istlah is often referred to for the meaning of fiqh (Nabhan, 1981: 13).Thus, Faruq Nabhan is already of the view that is... Faruq Nabhan who states that shari'a is everything that Allah preaches to his servant servant (Nabhan 1981: 10). But he further stated that, istlah is often referred to for the meaning of fiqh (Nabhan, 1981: 13). Thus, Faruq Nabhan has taken the view that the term shari'ah can be used for the meaning of fiqh, because many of the scholars use this term for this meaningthe most appropriate definition of the term shari'ah is that of Mahmud Syalthout, in his book al islam aqidah wa as sharia, namely